Mutations in the ARAP3 Gene in Three Families with Primary Lymphedema Negative for Mutations in Known Lymphedema-Associated Genes - Maurizio Ricci; Rita Compagna; Bruno Amato; Sercan Kenanoglu; Dominika Veselenyiova; Danjela Kurti; Mirko Baglivo; Syed Hussain Basha; Roberta Serrani; Giacinto Abele Donato Miggiano; Barbara Aquilanti; Giuseppina Matera; et al. (International Journal of Genomics)
Background. ARAP3 is a small GTPase-activating protein regulator, which has important functions in lymphatic vessel organogenesis and modulation of cell adhesion and migration. Mutations in the ARAP3 gene are associated with impaired lymphatic vessel formation. Objective. The aim of our study was to determine the genotypes of lymphedema patients in relation to variants in the ARAP3 gene in order to explore its role in the development of lymphedema. Methods and Results. We applied next-generation sequencing to DNA samples of a cohort of 246 Italian patients with lymphatic malformations. When we tested probands for known lymphedema genes, 235 out of 246 were negative. Retrospectively, we tested the DNA of these 235 patients for new candidate lymphedema-associated genes, including ARAP3. Three out of 235 probands proved to carry rare missense heterozygous variants in ARAP3. In the case of two families, other family members were also tested and proved negative for the ARAP3 variant, besides being unaffected by lymphedema. According to in silico analysis, alterations due to these variants have a significant impact on the overall structure and stability of the resulting proteins. Conclusions. Based on our results, we propose that variants in ARAP3 could be included in genetic testing for lymphedema.